2016
DOI: 10.3171/2015.9.spine153
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical treatment of sacral perineural (Tarlov) cysts: case series and review of the literature

Abstract: OBJECTIVE Tarlov cysts (TCs) occur most commonly on extradural components of the sacral and coccygeal nerve roots. These lesions are often found incidentally, with an estimated prevalence of 4%–9%. Given the low estimated rates of symptomatic TC and the fact that symptoms can overlap with other common causes of low-back pain, optimal management of this entity is a matter of ongoing debate. Here, the authors investigate the effects of surgical intervention on symptoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…However, regarding cyst enlargement, the ball-valve theory has achieved consensus as an underlying mechanism, suggesting that enlargement is caused by restricted CSF outflow from the cyst as a result of CSF pulsatile and hydrostatic forces [9, 10]. The first CT results in our case suggested that CSF inflow into the two cysts exceeded outflow, which supports this theory.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…However, regarding cyst enlargement, the ball-valve theory has achieved consensus as an underlying mechanism, suggesting that enlargement is caused by restricted CSF outflow from the cyst as a result of CSF pulsatile and hydrostatic forces [9, 10]. The first CT results in our case suggested that CSF inflow into the two cysts exceeded outflow, which supports this theory.…”
Section: Discussionsupporting
confidence: 69%
“…It was difficult to prove a causal relationship between the perineural cysts and the intercostal neuralgia; however, we concluded that the chest wall pain was caused by the pressure of the largest cyst at left T10 for several reasons: 1) this cyst was considerably larger and involved the nerve root fibers that were causing the symptoms; 2) this cyst showed an imbalance between CSF inflow and outflow; 3) because the pain was intermittent and alleviated when the patient was lying down, the cause of the pain was expected to be easily resolved, considering its relationship to head position; and 4) we found no other causal abnormality to explain the neuralgia other than the cyst. If the patient’s symptoms reappear in the future, we would reconsider invasive treatment as the patient would meet the criteria for surgery [9]. …”
Section: Discussionmentioning
confidence: 99%
“…Particularly promising outcomes have been associated with the use of microsurgical techniques which have been reported to provide symptomatic relief in up to 47.8%–86.6% of cases 21 22. However, it is important to note that these figures arise from studies with small sample sizes and are often retrospective in nature 21. Therefore, the generalisability of these findings to all patients is limited.…”
Section: Discussionmentioning
confidence: 99%
“…This is because of the fragility of the tissues and the elevated pressure in the spinal canal [10]. Finally, a high frequency of headaches might also reflect increased pressure in the cerebrospinal canal [1,2,8,11,18,33].…”
Section: Pathogenesismentioning
confidence: 99%
“…A MRI of the cervicodorsal spine was therefore reviewed, if available. Because the headaches that were often reported in our patient group might have reflected an increase in pressure inside the cerebrospinal canal [2,18], a complete ophthalmologic examination that included optic disc biometry was performed by an expert ophthalmologist. The examination used optical coherence tomography (Spectralis OCT, Heidelberg) and static automated perimetry (Humphrey Field Analyzer, Zeiss or Octopus 300, Heig-Streit) to detect and grade possible papilledema.…”
Section: Pathogenesismentioning
confidence: 99%